Market structure, bank conduct and bank performance: Evidence from ASEAN - Khan, Habib Hussain; Ahmad, Rubi; Chan, Sok Gee (Elsevier, 2018)
Whether banks in a concentrated market increase their profits through monopoly pricing is a question of prime concern for antitrust policies. We explore this question by introducing the role of bank conduct into the structure–performance relationship. We apply Two-step System GMM dynamic panel model to commercial banks in the Association of South East Asian Nations over the period of 1999–2014. The results indicate that the higher profits in concentrated banking industries are partially attributable to the anti-competitive conduct of banks. These findings are robust across alternative measures of market structure and bank conduct, and different time horizons. The implications of these findings require regulators to make sure that the consolidation policy for ASEAN is achieving its purpose – i.e. financial stability – and not allowing the banks to earn monopoly rents.